Delayed Treatment of Spinal Cord Injury In Young: A Case Report - Joshua Sutikno (Neurologico Spinale Medico Chirurgico, 2018)
Background: Spinal cord injury (SCI), one of the problems caused by traffic accidents, has a high morbidity in developing country like Indonesia. In Indonesia, the use of motorcycles is increasing every year. The epidemiological data from Fatmawati Hospital of spinal cord injury in 2014 was 104 cases both traumatic and non-traumatic SCI. In this case, a young boy with worsening of SCI, delayed the treatment for about 3 months. Case: A 19 years-old male complained of limbs paralysis for the past two weeks. He felt numbness and tingling in hamstring and calf areas. From past medical history, he had a motorcycle accident 3 months prior. After the accident, he suffered from extreme low back pain, but he could still move his legs. Due to economic restrictions, the patient refused to go to the hospital, and they chose a traditional treatment. For about three months, the pain was decreasing, but he was never pain-free. As the symptoms continued to worsen, the neurosurgeon decided to decompress the spinal cord and performed discectomy. After a week of treatment, the pain disappeared, motor muscle got better, and he could feel again the sensation on the dermatome of S1. Conclusion: Early treatment is recommended to get a better outcome. The surgery is not the only treatment, rehabilitation and orthotics using are important too. Delayed treatment increases morbidity rate.